Accelerated γ-face-centered cubic to ε-hexagonal close packed massive transformation in a laser powder bed fusion additively manufactured Co-29Cr-5Mo alloy. (1st April 2020) - Donkor, Boateng Twum; Song, Jie; Fu, Yao; Kattoura, Michael; Mannava, Seetha R.; Steiner, Matthew A.; Vasudevan, Vijay K.
Abstract: The γ-FCC (face-centered cubic) to ε-HCP (hexagonal close packed) phase transformation in a laser additively fabricated Co-29Cr-5Mo alloy was investigated. The microstructure of the as-built material was γ-FCC featured with a sub-micron scale dislocation cell structure and stacking faults. Aging at 1073 K led to rapid transformation within 0.5 h to the ε-HCP structure in a massive mode, characterized by: (i) composition invariance, (ii) oriented grain face nucleation; and (iii) interface-controlled linear growth mechanism. Effective lowering of the carbon content in the γ-FCC by partial tie-up as carbides along prior grain and dislocation cell boundaries and the diverse grain structure and interfaces are believed to promote the massive transformation. Graphical abstract: Image, graphical abstract